THE EFFECT OF CHANGE IN CATTLE PRICE ON THE DEMAND FOR INPUT AND THE SUPPLY OF OUTPUT IN THE BALI CATTLE FATTENING BUSINESS - Rusdianto, Sasongko Wijoseno (Informatika Pertanian, 2015)
The change in cattle price faced by farmers in the cattle fattening business when buying feeders and selling the beef cattle. This study was aimed to observe the efforts done by the farmers and the solutions that could be suggested. The purpose of this study was to analyze the effect of cattle price change on the demand for feeders and the supply of cattle which are produced by Bali cattle fattening businesses in West Nusa Tenggara. The results showed that the change of the beef cattle price on market level affect the demand for feeder cattle, which is one of the inputs fattening business. Instead the supply cattle of fattened does not effected by beef cattle price changes. Changes of the price of beef cattle on market level does not affect the supply of cattle fattened. Farmer income is determined by the price of cattle and price of fattened cattle and other costs incurred during the production process. It is concluded that the cattle price change affect to demand of feeder cattle with negative relation; but not influence to supply of beef cattle fattened.